Back Cover: A Host–Guest Electron Transfer Mechanism for Magnetic and Electronic Modifications in a Redox‐Active Metal–Organic Framework (Angew. Chem. Int. Ed. 18/2022). Issue 18 (5th April 2022) - Zhang, Jun; Kosaka, Wataru; Kitagawa, Yasutaka; Miyasaka, Hitoshi
Abstract : Host–guest electron transfer (HGET) plays a fundamental role in host–guest chemistry to modulate the functionality of molecular frameworks. In their Research Article (e202115976), Hitoshi Miyasaka and co‐workers introduce this concept for a redox‐active magnetic metal–organic framework, achieving a guest‐induced magnetic phase transition between a guest‐free antiferromagnet and a guest‐containing paramagnet, which may aid the design of novel porous magnets.